16th International Conference on Information Technology-New Generations (ITNG 2019) - Latifi, Shahram; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This 16th International Conference on Information Technology - New Generations (ITNG), continues an annual event focusing on state of the art technologies pertaining to digital information and communications. The applications of advanced information technology to such domains as astronomy, biology, education, geosciences, security and health care are among topics of relevance to ITNG. Visionary ideas, theoretical and experimental results, as well as prototypes, designs, and tools that help the information readily flow to the user are of special interest. Machine Learning, Robotics, High Performance Computing, and Innovative Methods of Computing are examples of related topics. The conference features keynote speakers, the best student award, poster award, service award, a technical open panel, and workshops/exhibits from industry, government and academia.
Networking and Wireless Communications -- Cybersecurity -- Data Mining -- Software Engineering -- High Performance Computing Architectures -- Computer Vision, HCI and Image Processing/Analysis -- Signal Processing, UAVs -- Health, Bioinformatics, Pattern Detection and Optimization -- Education, Applications and Systems -- Short Papers.
Keywords: Application software; Signal processing; Data structures (Computer science).; Information theory; Computer input-output equipment; Computer and Information Systems Applications; Signal, Speech and Image Processing; Data Structures and Information Theory; Input/Output and Data Communications